REORIENTASI TEORI PEMBELAJARAN PERSPEKTIF IMAM AL-GHAZALI: Aplikasi dan Kontekstualisasi Kitab Ihya’ Ulumuddin di Era Modern - Dozan, Wely; Hariadi, M. Farhan (Jurnal El-Hikam, 2022)
Lately, the discourse on the teori of Islamic education learning is increasingly developing in the perspective of Islamic thought as a transformation to make changes in the context of life. Education is an alternative solution in developing as well as developing learning according to an Islamic basis. So that not even when the thinking that has not have the thinking Islam when building arguments and statements in form design and concept learning, especially the implications for education in the modern world era. The focus of this research is to explore how the concept of learning in the perspective of Muslim figures, namely Imam Al-Ghazali and its contextualization in the Modern Era. There are several basic assumptions of this research. First, examine the concept of Islamic education. Second, the objectives and principles of Imam al-Ghazali education. Third, explore philosophical concepts of learning and relevance in the modern era. The type of research is literature study (Research Library) is library in nature. In summary, it is formulated that, Imam Al-Ghazali paid great attention and concern for education. In terms of the relevance of learning in order to instill the values ​​of discipline, responsibility, and the concept of learning according to the basis of the Qur'an which is oriented to the values ​​of Islamic teachings.